Ikigai and Urip iku Urub: A Comparative Study of Japanese and Javanese Philosophy - Purwandaru, R. Arief Toto; Suhartini (Jurnal Ilmiah WUNY, 2026)
Background: Japanese and Javanese are two languages rich in philosophy. One of the most prominent Japanese philosophies is "Ikigai," while in Javanese it is "Urip iku urup." These philosophies offer distinct yet potentially complementary perspectives on the concept of meaningful living. Objectives: This study aims to examine and compare the two philosophies based on their conceptual foundations and applications in everyday life. Method: This study employs a descriptive-qualitative approach. Data were collected through library research using texts related to the philosophies of "Ikigai" and "Urip iku urup," supplemented by observation based on the author's personal experience. Result: Both philosophies share a common emphasis on the importance of living a meaningful life, asserting that life extends beyond mere physical existence and holds values worth pursuing. The "Ikigai" philosophy centers on balancing passion, expertise, and personal financial fulfillment, as reflected in Japanese society's disciplined culture and in business models integrating passion, mission, vocation, and professionalism. The "Urip iku urup" philosophy, by contrast, prioritizes external goals oriented toward benefiting others, as exemplified by figures such as H.O.S. Tjokroaminoto and Peter Carey, and in various communal practices in Javanese society. Conclusion: Despite originating from geographically distant cultures, both philosophies are universal in nature and applicable across cultural boundaries.